2023
DOI: 10.1101/2023.01.13.523970
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spinal cord injury in mice amplifies anxiety: a novel light-heat conflict test exposes increased salience of anxiety over heat

Abstract: Spinal cord injury (SCI) predisposes individuals to anxiety and chronic pain. Anxiety- and pain-like behavior after SCI can be tested in rodents, yet commonly used tests assess one variable and may not replicate effects of SCI or sex differences seen in humans. Thus, novel preclinical tests should be optimized to better evaluate behaviors relating to anxiety and pain. Here, we use our newly developed conflict test - the Thermal Increments Dark-Light (TIDAL) test - to explore how SCI affects anxiety- vs. pain-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 40 publications
(50 reference statements)
0
3
1
Order By: Relevance
“…The SCI results are interesting in suggesting that dLAN interacts with SCI to enhance anxiety-like behavior. Previous studies— using various testing paradigms—have suggested that SCI alone amplifies anxiety-like behaviors (Fukutoku et al, 2020; Lee et al, 2023a) including a reduction in juvenile social interactions in rats (do Espírito Santo et al, 2019), whereas our results with JSE show that SCI mice housed in LD have similar anxiety-like behaviors as sham-LD mice. Further, mice with SCI exposed to dLAN display amplified anxiety-like behavior compared to SCI-LD mice ( Fig.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…The SCI results are interesting in suggesting that dLAN interacts with SCI to enhance anxiety-like behavior. Previous studies— using various testing paradigms—have suggested that SCI alone amplifies anxiety-like behaviors (Fukutoku et al, 2020; Lee et al, 2023a) including a reduction in juvenile social interactions in rats (do Espírito Santo et al, 2019), whereas our results with JSE show that SCI mice housed in LD have similar anxiety-like behaviors as sham-LD mice. Further, mice with SCI exposed to dLAN display amplified anxiety-like behavior compared to SCI-LD mice ( Fig.…”
Section: Discussioncontrasting
confidence: 81%
“…Individuals with SCI commonly experience a higher prevalence of anxiety, depression, and various mood disorders compared to the general population (Kessler et al, 2012;Lim et al, 2017;Peterson et al, 2020). Likewise, post-SCI anxiety-like and depression-like symptoms occur in clinically-relevant rodent models (Luedtke et al, 2014;Farrell and Houle, 2019;Fukutoku et al, 2020;Lee et al, 2023a) with neuroinflammation as a key factor (Wu et al, 2014b(Wu et al, , 2014aMaldonado-Bouchard et al, 2016;do Espírito Santo et al, 2019;Brakel et al, 2021). Furthermore, dLAN and other circadian disruptions can induce changes in anxiety-like and depression-like behaviors independently of any surgical intervention (Bedrosian et al, 2013;Borniger et al, 2014;Cissé et al, 2016;Chen et al, 2021bChen et al, , 2021a.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, it is important to identify mechanistic differences across genders that underlie susceptibility to anxiety and comorbid conditions. We used the TIDAL conflict test previously to evaluate anxiety-like behavior of mice with spinal cord injury, which revealed that mice with spinal cord injury exhibited increased anxiety-like behavior relative to sham surgery controls (Lee et al, 2023). To confirm that results obtained using the TIDAL conflict test measure anxiety-like behavior, here we sought to further validate the TIDAL conflict test using known pharmacologic agents that ameliorate anxiety-like behavior.…”
Section: Discussionmentioning
confidence: 99%
“…We used the TIDAL conflict test previously to evaluate anxiety-like behavior of mice with spinal cord injury, which revealed that mice with spinal cord injury exhibited increased anxiety-like behavior relative to sham surgery controls (Lee et al, 2023). Here, we sought to further validate the TIDAL conflict test using known pharmacologic agents that ameliorate anxiety-like behavior.…”
Section: Discussionmentioning
confidence: 99%